Dietary L-Tryptophan Modulates the Structural and Functional Composition of the Intestinal Microbiome in Weaned Piglets - Liang, Haiwei; Dai, Zhaolai; Liu, Ning; Ji, Yun; Chen, Jingqing; Zhang, Yunchang; Yang, Ying; Li, Ju; Wu, Zhenlong; Wu, Guoyao (Frontiers in Microbiology, 2018)
Background: Intestinal microbiota play an important role in regulating metabolism, physiology, and immune response of the host. L-Tryptophan (Trp) are metabolized by several genera of the intestinal flora. It remains largely unknown whether Trp can regulate the composition and diversity of the intestinal microbiota or contribute to intestinal homeostasis. Methods: A total of 126 weaning piglets were fed a corn- and soybean meal-based diet supplemented with 0, 0.2 or 0.4% Trp for 4 wk. The intestinal microbiota was measured by using bacterial 16S rRNA gene-based high-throughput sequencing methods. Metabolites of Trp and short-chain fatty acids (SCFAs) in the hindgut were determined by high-performance liquid chromatography and gas chromatography, respectively. The mRNA levels for aromatic hydrocarbon receptor (AhR), tumor necrotic factor-α (TNF-α), Interleukin-8 (IL-8), and protein abundances of tight junction proteins were determined. Results: Compared with the control group, Trp supplementation enhanced piglet growth performance and markedly altered the intestinal microbial composition as evidenced by enhanced alpha and beta diversity in the microbiome (P < 0.05). The abundances of Prevotella, Roseburia, and Succinivibrio genera were enriched, but those of Clostridium sensu stricto and Clostridium XI, opportunistic pathogens, were decreased with dietary Trp supplementation. Analysis of metabolic pathways indicated enhanced indole alkaloid biosynthesis and Trp metabolism, which was validated by elevated concentrations of 3-indoleacetic acid and indole, as well as in the intestinal contents of Trp-supplemented piglets (P < 0.05). These changes in Trp metabolites were correlated with activation of AhR and cytochrome p4501 A1 (CYP1A1) in cecum and colon tissues, and decreased TNF-α and IL-8 mRNA levels. Moreover, the protein abundances for zonula occluden (ZO)-1 and occludin were upregulated by Trp supplementation in colonic tissues. Conclusions: Dietary Trp supplementation altered intestinal microbial composition and diversity, improved intestinal mucosal barrier function, activated AhR signaling, and downregulated expression of inflammatory cytokines in the intestine of weaned piglets. These results indicate a crosstalk between dietary Trp and intestine in nutrition, microbial metabolism and mucosal immunity.